(untitled) (Research, Society and Development, 2022)
Microbial infections, since the dawn of humanity, are described as major problems faced by populations. Faced with many of them, several civilizations suffered without having, at least, knowledge about what affected them. Furthermore, it is noted that these losses arising from infectious diseases did not only afflict humans, but also had a burden on animal communities and the environment as a whole. However, after a long time of study and development in the medical field, antimicrobial drugs were developed, which revolutionized the techniques hitherto known to combat these various pathogens. Therefore, many of these drugs began to be prescribed indiscriminately to combat or prevent certain diseases, which led to the onset of Antimicrobial Resistance (AMR), a fact that generated intense discussions around the world. By taking note of this, we sought, through this, to deepen the knowledge about the entire biological process intrinsic to this mechanism of natural selection of certain aggressor organisms. Thus, the present study aimed to develop a knowledge network that interconnects the factors associated with antimicrobial resistance with better knowledge of antimicrobials, their effects and limits of use. Therefore, for antibacterials to continue to be effective and exert their function in human, animal and environmental health, it is important to adopt control measures on the prescription of certain compounds, in order to avoid potential adaptation and resistance of undesirable beings.